Effects of Dietary Grape Seed Meal Bioactive Compounds on the Colonic Microbiota of Weaned Piglets With Dextran Sodium Sulfate-Induced Colitis Used as an Inflammatory Model - Grosu, Iulian A.; Pistol, Gina C.; Marin, Daniela E.; Cişmileanu, Ana; Palade, Laurenţiu M.; Ţăranu, Ionelia (Frontiers in Veterinary Science, 2020)
Microbiota affects host health and plays an important role in dysbiosis. The study examined the effect of diet including grape seed meal (GSM) with its mixture of bioactive compounds on the large intestine microbiota and short-chain fatty acid synthesis in weaned piglets treated with dextran sodium sulfate (DSS) as a model for inflammatory bowel diseases. Twenty-two piglets were included in four experimental groups based on their diet: control, DSS (1 g/kg/b.w.+control diet), GSM (8% grape seed meal inclusion in control diet), and DSS+GSM (1 g/kg/b.w., 8% grape seed meal in control diet). After 30 days, the colon content was isolated and used for microbiota sequencing on an Illumina MiSeq platform. QIIME 1.9.1 pipeline was used to process the raw sequences. Both GSM and DSS alone and in combination affected the diversity indices and Firmicutes:Bacteroidetes ratio, with significantly higher values in the DSS-afflicted piglets for Proteobacteria phylum, Roseburia, Megasphera and CF231 genus, and lower values for Lactobacillus. GSM with high-fiber, polyphenol and polyunsaturated fatty acid (PUFA) content increased the production of butyrate and isobutyrate, stimulated the growth of beneficial genera like Prevotella and Megasphaera, while countering the relative abundance of Roseburia, reducing it to half of the DSS value and contributing to the management of the DSS effects.